Efforts to Improve Student Learning Outcomes in the Volleyball Bottom Passing Learning Process Through the Use of the Demonstration Method in Class VIII-9 UPT SPF SMP Negeri 2 Sunggal Academic Year 2022/2023 - Polmer Siagian (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to find out how to improve learning outcomes for UPT SPF SMP Negeri 2 Sunggal, especially class VIII-9 so that through the use of the demonstration method, it can influence learning outcomes for Physical Education lessons. This research uses a quantitative approach using the demonstration method. The subjects in this research were students in class VIII-9 at UPT SPF SMP Negeri 2 Sunggal for the 2022/2023 academic year, totaling 31 students consisting of 16 male and 15 female students. The data collection technique was carried out using the technique of percentage of individual absorption capacity and classical completeness, namely: individually at least 25% and classically 100%. And by conducting observations with teachers regarding the implementation of learning through the use of demonstration methods and observing students. The results of this research are (1) Improving student learning outcomes in completing Physical Education questions in class VIII-9 UPT SPF SMP Negeri 2 Sunggal for the 2022/2023 academic year. This can be seen from the results of observations of learning methods during demonstrations by these students. The results of the cycle were obtained. I and II cycles, namely: 4% and 21% (2) Applying the demonstration method in class VIII-9 for the 2022/2023 academic year can improve learning outcomes in the volleyball bottom passing learning process. This can be seen from the results of the students' learning outcomes. The results obtained from cycle I and cycle II were: 4% and 21%.